The impact of apartment furniture design on children’s development and recommendations for multifunctional furniture - Mahimma Romadhona; Ahadiat Joedawinata (Pascasarjana Institut Seni Indonesia Surakarta, 2023)
People residing in urban environments, particularly children inhabiting apartments, often contend with limited space for movement. Children require sufficient space for physical activity to support their physical and psychological development. This study analyzes furniture design's influence on children's development. It employs a qualitative research approach with a phenomenological orientation and descriptive analysis. The data collection methods employed in this study encompass literature review, observation, and interviews. The study's participants consist of infants (newborn to 18 months) and toddlers (18 to 36 months) residing in apartments within Kalibata City, along with their caregivers. The study's findings indicate that furniture within confined spaces is not adequately tailored to children's activities and needs, consequently negatively impacting their physical and psychological well-being. Therefore, a furniture redesign to accommodate children's activities and support their development is imperative. This research recommends optimizing furniture design, encompassing construction systems, materials, safety measures, dimensions, and age-appropriate usage. The insights gleaned from this study hold significant value for the real estate industry, furniture design sector, interior design profession, and consumers.